Comparative Analysis of the C4.5 Algorithm and the Nearest Neighbor for the Number of Prospective New Student Registrants - Wati, Nursetia; Ibrahim, Irawan (International Journal Papier Advance and Scientific Review, 2021)
In 2015, the number of registrants for new student candidates at Muhammadiyah University of Gorontalo, has increased about 20% - 50% from the last year in 2014, but when it starts from 2017/2018 of the academic year the number of new student candidates who registered was only around 4,713 students for bachelor’s and there is 1,256 students for Bachelor’s Degree, while in the academic year of 2018/2019 bachelor’s degree students were only 765 and bachelor’s students were around 4,187, it is known as a decline from the previous year. This study, aims to help to predict the number of prospective of the new students who will enroll in the following of the academic year by analyzing the comparison of the C4.5 and Nearest Neighbor Algorithms with comparing two of algorithms to get the best results. In the C4.5 and Nearest Neighbor Algorithms, it is necessary to be able to see some patterns from the data about the prospective students, then, they can produce the predictions of the number of prospective students who can help in increasing the number of prospective students that is according to the target achievements of Muhammadiyah University of Gorontalo (UMG) itself.